The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.joc.9b02873
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polysubstituted Trifluoromethylpyridines from Trifluoromethyl-α,β-ynones

Abstract: A novel and efficient method for synthesis of polysubstituted trifluoromethylpyridine derivatives by the Bohlmann–Rahtz heteroannulation reaction is described, which use trifluoromethyl-α,β-ynones as trifluoromethyl building blocks to react with β-enamino esters or β-enamino ketones in the presence of ZnBr2 to form the trifluoromethylpyridine derivatives in good yields. The protocol has the advantages of readily available starting materials, mild reaction conditions, and high atom economy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…[27,28] In 2020 and 2021, a novel and efficient method for synthesis of trifluoromethylpyridines 5 and 7, trifluoromethyl-quinolines 10, or trifluoroacetyl-quinoline derivatives 12 from the reactions of trifluoromethyl-α,β-ynones 3 with β-enamino esters (or ketones) 4, vinyl azides 6, acetanilides 8, anilides, 9 or quinolines 11 in the presence of ZnBr 2 , CuBr 2 /PPh 3 / PMDETA, [RhCp*Cl 2 ] 2 /AgSbF 6 , or morpholine was described by the groups of Hu, Trofimov, Nenajdenko, Wu, Wang, and Cheng (Scheme 3). [10,[29][30][31] The results indicated that the reactions between trifluoromethyl-α,β-ynones 3 and β-enamino esters (or ketones) 4 catalyzed by ZnBr 2 gave 40-82% yields of trifluoromethyl-pyridines 5 except when R 2 in substrates 4 was CF 3 . [10] The cyclization of vinyl azides 6 with CF 3 -ynones 3 catalyzed by CuBr 2 in the presence of PPh 3 and pentamethyldiethylenetriamine (PMDETA) in dimethyl sulfoxide (DMSO) and PhMe at room temperature for 12 hr furnished 2,4-diaryl-6-trifluoromethylated pyridines 7 in 35-65% yields.…”
Section: Synthesis Of Trifluoromethylpyridines Trifluoromethyl-quinol...mentioning
confidence: 99%
See 3 more Smart Citations
“…[27,28] In 2020 and 2021, a novel and efficient method for synthesis of trifluoromethylpyridines 5 and 7, trifluoromethyl-quinolines 10, or trifluoroacetyl-quinoline derivatives 12 from the reactions of trifluoromethyl-α,β-ynones 3 with β-enamino esters (or ketones) 4, vinyl azides 6, acetanilides 8, anilides, 9 or quinolines 11 in the presence of ZnBr 2 , CuBr 2 /PPh 3 / PMDETA, [RhCp*Cl 2 ] 2 /AgSbF 6 , or morpholine was described by the groups of Hu, Trofimov, Nenajdenko, Wu, Wang, and Cheng (Scheme 3). [10,[29][30][31] The results indicated that the reactions between trifluoromethyl-α,β-ynones 3 and β-enamino esters (or ketones) 4 catalyzed by ZnBr 2 gave 40-82% yields of trifluoromethyl-pyridines 5 except when R 2 in substrates 4 was CF 3 . [10] The cyclization of vinyl azides 6 with CF 3 -ynones 3 catalyzed by CuBr 2 in the presence of PPh 3 and pentamethyldiethylenetriamine (PMDETA) in dimethyl sulfoxide (DMSO) and PhMe at room temperature for 12 hr furnished 2,4-diaryl-6-trifluoromethylated pyridines 7 in 35-65% yields.…”
Section: Synthesis Of Trifluoromethylpyridines Trifluoromethyl-quinol...mentioning
confidence: 99%
“…[10,[29][30][31] The results indicated that the reactions between trifluoromethyl-α,β-ynones 3 and β-enamino esters (or ketones) 4 catalyzed by ZnBr 2 gave 40-82% yields of trifluoromethyl-pyridines 5 except when R 2 in substrates 4 was CF 3 . [10] The cyclization of vinyl azides 6 with CF 3 -ynones 3 catalyzed by CuBr 2 in the presence of PPh 3 and pentamethyldiethylenetriamine (PMDETA) in dimethyl sulfoxide (DMSO) and PhMe at room temperature for 12 hr furnished 2,4-diaryl-6-trifluoromethylated pyridines 7 in 35-65% yields. [29] Trifluoromethyl-quinolines 10 were synthesized in moderate to excellent yields from trifluoromethyl-α,β-ynones 3 and acetanilides 8 or anilides 9 through the catalysis of [RhCp*Cl 2 ] 2 and AgSbF 6 in 1,2-dichloroethane (DCE) at 100 C for 3 hr (8 giving 50-99% yields, 9 giving 68-96% yields).…”
Section: Synthesis Of Trifluoromethylpyridines Trifluoromethyl-quinol...mentioning
confidence: 99%
See 2 more Smart Citations
“…179 In particular, trifluoromethyl-α,β-ynones have been studied for the formation of various heterocycles, especially fluorinated N-heterocycles in organic synthesis. [180][181][182] In this context, Wang and co-workers have reported the synthesis of 2-trifluoromethylated quinolines 239 in a regioselective fashion through Rh(III)-catalysed C-H activation via redoxneutral [3 + 3] annulation between anilines and CF 3 -ynones 238 using an acetyl moiety as a traceless directing group (Scheme 45a). 183 The reaction conditions required [RhCp*Cl 2 ] 2 (2.0 mol%) and AgSbF 6 (8.0 mol%) in DCE at 100 °C for 3 h to furnish the desired 2-trifluoromethylated quinolines 239 with high regioselectivity.…”
Section: Trifluoromethyl-αβ-ynonesmentioning
confidence: 99%